Perception regarding pubertal changes among rural adolescent boys of Haryana: A school based study - Chayal, Vinod; Khanna, Pardeep; Verma, Ramesh (Indian Journal of Community Health, 2016)
Background: Adolescence is a transition phase through which a child matures into an adult. The physical changes in the human body are from infant to child to adolescence to adult to old age. All phases of life behave like a coin with both good and bad facets attached to each phase of life. Aims & Objectives: 1. To study perception and awareness regarding pubertal changes among school going adolescent boys. 2. To study the association between education and perceived pubertal problems among study subjects. Material & Methods: The study was conducted among male students of senior secondary schools of community development block Beri in one year. The study universe comprised of students in middle and late adolescence (aged 14-18 years) studying in 9th to 12th classes of the senior secondary schools in the area. A total of 1000 male students were selected from these schools which were more than the required sample size of 891. Results: The study found that 42.66% students and a half (50%) of students of class 9th & 10th and class 11th & 12th respectively considered that pubertal changes as a normal phenomenon. The majority of students admitted practicing masturbation and felt shy and guilty for practicing masturbation, also students felt fatigued after night emission. Conclusions: The study concludes that adolescent’s sexuality which often causes controversy and concern among adults is least discussed with them during adolescence. The reasons for this may be many, including moral grounds or because of concomitant health risks and threats to wellbeing.